2018
DOI: 10.3389/fpsyg.2018.01815
|View full text |Cite
|
Sign up to set email alerts
|

Creative Argumentation: When and Why People Commit the Metaphoric Fallacy

Abstract: This article aims to understand when and why people accept fallacious arguments featuring metaphors (metaphoric fallacy) as sound arguments. Two experiments were designed to investigate, respectively, when and why participants fell into the metaphoric fallacy. In the first experiment, participants were provided with a series of syllogisms, presented in natural language, containing in their first premise either a lexically ambiguous, literal middle term or a metaphorical middle term, i.e. the term that “bridges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 113 publications
0
4
0
2
Order By: Relevance
“…The metaphorical frame does not directly influence reasoning (as instead was found by Thibodeau and Borodisky [66,67]), but provides a more nuanced set of communicative effects. While metaphor was found to influence participants' acceptance of the conclusion in the case of syllogisms in narrow contexts [17], this effect seems lost in the case of wider contexts, where the persuasive effects of the text prevail over the argument evaluation. Also, metaphor use is not a predictor of higher vaccination intentions, as instead was found by Scherer and colleagues [54].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The metaphorical frame does not directly influence reasoning (as instead was found by Thibodeau and Borodisky [66,67]), but provides a more nuanced set of communicative effects. While metaphor was found to influence participants' acceptance of the conclusion in the case of syllogisms in narrow contexts [17], this effect seems lost in the case of wider contexts, where the persuasive effects of the text prevail over the argument evaluation. Also, metaphor use is not a predictor of higher vaccination intentions, as instead was found by Scherer and colleagues [54].…”
Section: Discussionmentioning
confidence: 91%
“…Still, it is an open question whether and how the reasoning process and the metaphorical framing might creatively interact. For instance, in simple deductive tasks, Ervas and colleagues [17] showed that conventional metaphors, whose meaning is lexicalized and so familiar that goes unnoticed by participants, can be revitalized to hold a plausible conclusion of the argument, while novel metaphors, whose meaning is so new and creative that are fast recognized as metaphorical, rather lead to think about alternative conclusions.…”
Section: Metaphor As a Reasoning Devicementioning
confidence: 99%
“…Still, it is an open question whether and how the reasoning process and the metaphorical framing might creatively interact. For instance, in simple deductive tasks, Ervas et al (2018) showed that conventional metaphors, whose meaning is lexicalized and so familiar that goes unnoticed by participants, can be revitalized to hold a plausible conclusion of the argument, while novel metaphors, whose meaning is so new and creative that are fast recognized as metaphorical, rather lead to think about alternative conclusions.…”
Section: Metaphor As a Reasoning Devicementioning
confidence: 99%
“…De igual forma, la retórica moderna, si bien se desliga desde su teleología de la clásica, centra su interés en el ámbito jurídico (Feteris, 2017) y en otros entornos más cercanos a la ciencia (Erduran et al, 2015); así, se traza una ruta que parte del raciocinio y cumple con elementos garantes y descriptivos o explicativos que encajan con aceptación en las ciencias exactas, naturales e ingenieriles (Charwat et al, 2015), pero que no son asumidas discursivamente por las comunidades en sus actos comunicativos de interacción y socialización (Ervas et al, 2018).…”
Section: Relación De Situaciones Socialmente Punibles O No Deseadas C...unclassified
“…Por consiguiente, las comunidades fortalecen las tradiciones discursivas propias y aprendidas de sus entornos sociales y las relacionan con lo que entienden por retórica y argumentación (Rodríguez, 2019); es decir, no hay una diferencia significativa entre estos dos conceptos, pues los asumen como sinónimos (García et al, 2018) y, además, los resemantizan con sus apreciaciones sobre lo que significa argumentar (Ervas et al, 2018).…”
Section: Relación De Situaciones Socialmente Punibles O No Deseadas C...unclassified